Massive left atrial calcification - Masaki Monden; Daisuke Fukamachi; Naoya Matsumoto; Yasuo Okumura (Clinical Case Reports, 2023)
Abstract We reported this case because calcification of the mitral valve is a common complication of rheumatic fever, but calcification of the left atrium is rare.